2013
DOI: 10.1596/1813-9450-6542
|View full text |Cite
|
Sign up to set email alerts
|

China's 2008 Labor Contract Law: Implementation and Implications for China's Workers

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 13 publications
5
56
0
1
Order By: Relevance
“…This is a very crude and probably unsatisfactory approach given that it conflates contract status with other job attributes. Other research has found that the share of "formal" workers with labor contracts increased after the Law was implemented (Gallagher et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is a very crude and probably unsatisfactory approach given that it conflates contract status with other job attributes. Other research has found that the share of "formal" workers with labor contracts increased after the Law was implemented (Gallagher et al, 2014).…”
mentioning
confidence: 99%
“…This is a very crude and probably unsatisfactory approach given that it conflates contract status with other job attributes. Other research has found that the share of "formal" workers with labor contracts increased after the Law was implemented (Gallagher et al, 2014).The difference-in-difference specification comparing impacts on formal employees and temporary employees while controlling for macro labor conditions produces quite different †Correspondence: …”
mentioning
confidence: 99%
“…Furthermore, the law is often intentionally ambiguous, leaving it to local and national leaders to interpret. Finally, laws and interpretations are only as good as the enforcement (Gallagher et al 2015), which requires a different set of institutions and resources than those required to make laws (Gallagher and Dong 2011). Thus, laws are not an adequate tool for limiting precarisation or limiting worker vulnerability, and this holds true across different national contexts.…”
Section: Sarah Swidermentioning
confidence: 99%
“…Foreign and domestic business interests weighed in as well, generally seeking to strengthen the rights of employers vis-a-vis workers. The American Chamber of Commerce expressed serious concern that the law would be enforced more stringently in foreign-owned firms than in domestic ones (Freeman and Li 2013;Gallagher et al 2013;Pringle 2011).…”
Section: Overview Of the 2008 Labor Contract Lawmentioning
confidence: 99%
“…Surveys in 2009 and 2010 found that most workers were aware of the legislation, at least in general terms. The number of workers covered by labor contracts increased significantly (Freeman and Li 2013, 8;Gallagher et al 2013). Because the Labor Contract Law provides that contracts cover not only wages and work conditions, but social insurance protection as well, the law increased the number of workers who were enrolled in pension and other social insurance plans (Gallagher et al 2013).…”
mentioning
confidence: 99%